Informal caregivers' quality of life and management strategies following the transformation of their cancer caregiving role: A qualitative systematic review - Yingying Cai; Alison Simons; Samantha Toland; Junfeng Zhang; Kexin Zheng (Elsevier, 2021)
Objectives: Globally, informal caregivers caring for cancer patients meet challenges within their caregiving role, which significantly influence their quality of life. This qualitative systematic review aimed to analyze how cancer caregiving influence the quality of life of informal caregivers and the management strategies of informal caregivers for their role as cancer caregivers. Methods: Following the enhancing transparency in reporting the synthesis of qualitative research (ENTREQ) statement, Wanfang database, the China National Knowledge Infrastructure (CNKI), CINAHL, MEDLINE, PubMed, Cochrane Library, PsycARTICLES and PsycINFO, and grey literature in English and Chinese from 1 May 2009 to 31 December 2019 were searched. Quality of included studies was assessed by the Critical Appraisal Skills Programme (2018) Qualitative Checklist and thematic synthesis was conducted. Results: Of the 8,945 studies identified, 6 studies met the inclusion criteria. One analytical theme relating to the QoL of informal caregivers following cancer caregiving was identified: "challenges of caregiving". In terms of the management strategies to the role of cancer caregivers, two analytical themes were identified: "self-adjustment" and "seeking for formal and informal support". Conclusions: Cancer caregiving influences informal caregivers' QoL significantly and informal caregivers develop diverse coping strategies to deal with the difficulties occurred while balancing the relationship between their own lives and caregiving. However, professional and policy support remain inadequate for informal caregivers that require the need for improvement in terms of health care professionals and policymakers.